Association of homocysteine (but not of MTHFR 677 C>T, MTR 2756 A>G, MTRR 66 A>G and TCN2 776 C>G) with ischaemic cerebrovascular disease in Sicily - Bosco, Paolo; Guéant-Rodriguez, Rosa-Maria; Anello, Guido; Spada, Rosario; Romano, Antonino; Fajardo, Adrian; Caraci, Filippo; Ferri, Raffaele; Guéant, Jean-Louis (Thrombosis and Haemostasis, 2006)
Association between methylenetetrahydrofolate reductase polymorphism (MTHFR 677 C>T), a determinant of homocysteine plasma level (t-Hcys), with ischaemc cerebrovascular disease (iCVD) seems to be neutral in North Europe and North America. The association of 2756 A>G of methionine synthase (MTR), 66 A>G of methionine synthase reductase (MTRR) and 776 C>G of transcobalamin (TCN2) needs to be evaluated further. It was the objective of this study to evaluate the association of these polymorphisms, t-Hcys, vitamin B12 and folate levels with iCVD, in an Italian population from Sicily. We investigated the association of these polymorphisms, t-Hcys, vitamin B12 and folate with iCVD in 252 subjects, including 131 cases and 121 sexand agematched healthy controls. t-Hcys was higher in the iCVD group than in controls [15.3 (11.5–17.9) vs. 11.6 (9.4–14.5) µM; P=0. 0007] and also in subjects withTCN2 776CG genotype, compared to homozygous genotypes [13.5 (9.9± 16.9) vs. 11.7 (9.6 ± 14.4) µM; P=0. 0327]. The folate level in cases and controls was consistent with an adequate dietary intake [12.7 (9.0–15.3) vs. 12.5 (9.6–16.9) nM; P=0. 7203]. In multivariate analysis, t-Hcys was a significant independent predictor of iCVD with an odds ratio of 1.14 (95% C.I. : 1.06–1.24; P=0. 0006). No association was found between MTHFR, MTR, MTRR and TCN2 polymorphisms and iCVD risk. We have found an influence of t-Hcys and a neutral effect of MTHFR, MTR, MTRR and TCN2 on iCVD risk in Sicily. The neutral influence of these polymorphisms may be explained by adequate status in folate and vitamin B12. Other factors underlying the increased t-Hcys need further investigations.
Keywords: Cerebrovascular disease; folate; homocysteine; methionine synthase reductase; methylenetetrahydrofolate reductase; transcobalamin